Lewis acid catalysed polymerisation of cyclopentenone - Dissanayake, Deepamali; Draper, Alysia; Liu, Zhizhou; Jaunnoo, Neelofur; Haven, Joris J; Forsyth, Craig; McKay, Alasdair I; Junkers, Tanja; Vidovi, Dragoslav (Chemical science (Cambridge), 2024)
A modest structural change of a β-diketiminate-supported aluminium complex leads to dramatic differences in the reactivity towards cyclopentenone. While the bulkier complex efficiently executes Diels Alder transformations the smaller analogue performs unique polymerisation of this substrate. This observation appears to be unprecedented in the chemistry of Lewis acids and cyclic dienophiles as it represents a unique way to polymerise a functionalised olefin. A modest structural change of a β-diketiminate-supported aluminium complex leads to dramatic differences in the reactivity towards cyclopentenone.